The social phenomenon of trolling: understanding the discourse and social practices of online provocation. Issue 11 (24th July 2021) - Demsar, Vlad; Brace-Govan, Jan; Jack, Gavin; Sands, Sean
ABSTRACT: Despite its benefits, the online environment fosters darker consumer behaviours including conflict, revenge, and aggression. Trolling has recently entered the marketing lexicon and poses a substantial threat for consumers and brands. However, current understandings of trolling are limited by a lack of empirical research, and a focus on undiscernible 'trolls' and their behaviours. Accordingly, the term 'trolling' has become a catch-all to describe almost any online misbehaviour. This research takes a broader perspective by examining the historical and discursive conditions that have produced trolling and its social practices. Combining a Foucauldian archaeology with marketing practitioner interviews, this study contributes a comprehensive understanding of trolling as a social phenomenon, the social practices that constitute it, and how trolling is enacted within consumer-brand interactions.